PERAN MAHASISWA PART TIME DALAM MANAJEMEN KOLEKSI DI PERPUSTAKAAN UNIVERSITAS ISLAM INDONESIA YOGYAKARTA - Hana Isnaini Al Husna (Jurnal Pustaka Ilmiah, 2019)
Writing in this paper aims to see further which role or expected role of part-time students or workers who calculate the time in collection management or collection development in the Directorate of Library UII Yogyakarta. This needs to be seen because there are still many universities in Indonesia that still lack librarians, while librarians themselves have been more involved in fields that can be termed managers. In this paper will be examined to what extent part-time students are involved in collection management, is it possible to develop it to assist in the collection policy domain. The method used in this study is qualitative by means of interviews and observations. Based on observations and interviews, the involvement of part time students in the collection management process in the UII Library Directorate is limited to assisting technical problems, for involvement in policies all handled by the leadership in this case is the Library Director and Division Head in the UII Library. In this research, the author sees that it can still be developed the participation of the involvement in the policy making process, as an example that part time students are also users so that their opinions or ideas can be raised from them to create a collection development policy that is flexible and user friendly.